Economic analysis on innovation of public lighting system in Rosana city (Research, Society and Development, 2021)
This research suggests the preparation of an efficient street lighting (IP) project, taking into account the technical-financial feasibility of the luminaires that make up the IP system in Rosana city. the study is presented to raise the saving potential in the consumption of electrical energy and in the amount paid monthly with ip. the work's purpose is to replace conventional luminaires (sodium steam), which has a short median life and greater energy consumption, by led luminaires (Light Emitting Diode) which have a longer average lifespan and are more efficient. The economic analysis was done based on standard indicators of investment feasibility, such as net present value (VPL), discounted payback and internal rate of return (TIR). Finally, presents data analysis with the purpose of optimizing the sl system and reducing electric energy consumption in the Rosana city.